PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR - Silaban, Adeline; Muhammad Akbar; Siti Hajar; Paulus G D Lasmono; Rispah Purba; Desy C Silaban; Silvia Anggri Wijaya (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
A study was conducted to determine (1) the Improvement of students' learning outcomes in the material of motion of objects, and (2) the influence of problem-based learning models on learning outcomes of physics concepts. The type of research used was quantitative using one group pre-test and post-test design. The population in this study were students of class VII A at SMP YPK Diaspora Kotaraja, with a sample of 30 students. In this method, teaching and learning activities began with a pre-test then given treatment using a problem-based learning model, and then at the end of the learning activity a post-test was given. The instruments used in collecting data were questionnaires and objective tests. The data analysis technique used the n-gain test and regression test. The results obtained from this study were: (1) the results of the N-gain test comparing the average pretest-posttest so that the N-gain score was 0.63, included in the moderate category. This means that there was an increase in students' learning outcomes. (2) the results of the regression test with a significant value of 0.004 <0.05. It is concluded that the problem-based learning model has a significant influence on improving learning outcomes